Establishment of efficient hypocotyl-derived protoplast isolation and its application in soybean (Glycine max [L.] Merr.) - Kim, Kihwan; Shin, Junseop; Lee, Jeong-Dong; Kim, Won-Chan (Frontiers in Plant Science, 2025)
Soybean is important crop species in agriculture, food science, and biotechnology due to their valuable components. The exploration of soybean genetic traits is being highlighted for the advancement of research in various aspects. The utilization of plant biotechnology, plant protoplast techniques, for the study of genetic characteristics is being extended to various agricultural crop species. The quintessential goal of genetic characterization utilizing plant protoplasts encompasses the provision of stable plant protoplasts alongside the establishment of transfection condition. Despite the numerous studies on protoplast isolation, standardized and reliable soybean protoplasts protocols for comprehensive investigations into the intricate regulatory mechanisms governing immune responses, cellular processes, and developmental pathways remain insufficiently established. In this study, we propose an efficient methodology for the protoplast isolation and the PEG-Ca2+ mediated transfection of soybean [Glycine max (L.) Merr.] cultivar (Williams 82). The protoplast isolation entailed the evaluation of variables including mannitol concentration, enzyme mixture composition, and enzymatic digestion duration. The optimal conditions for hypocotyl-derived protoplast isolation were identified as 0.4 M mannitol, an enzyme mixture containing 1.5% (w/v) cellulase and 0.4% (w/v) macerozyme, and an 8-hour enzymatic digestion period, resulting in high viability and protoplast yield (>3.0 × 106/g FW). For the PEG-Ca2+ mediated transfection process, the parameters assessed including PEG concentration, plasmid quantify or purified recombinant proteins, and PEG-Ca2+ incubation duration. The validation of the reliability of hypocotyl-derived protoplast system through transient gene expression demonstrates its utility as a robust platform for analysis of genetic traits in soybean. This could extend the scope of application to understanding the cell-to-cell interactions for physiological responses in soybean.